2007
DOI: 10.1111/j.1468-0297.2007.02094.x
|View full text |Cite
|
Sign up to set email alerts
|

Real and Nominal Wage Rigidities and the Rate of Inflation: Evidence from West German Micro Data

Abstract: Bibliografische Information Der Deutschen BibliothekThe paper examines real and nominal wage rigidities. We estimate a switching regime model, in which the observed distribution of individual wage changes, computed from West German register data for 1976-1997, is generated by simultaneous processes of real, nominal or no wage rigidity, and measurement error. The fraction of workers facing wage increases that are due to nominal, but mostly real wage rigidity is substantial. The extent of real rigidity rises wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
3

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 16 publications
5
87
3
Order By: Relevance
“…These distributions are characterized by a bunching of wage changes at exactly zero; there are some wage changes just above zero in these distributions, but almost no wage changes just below. 68 Careful studies have documented such wage stickiness in Australia, Canada, Germany, Japan, Mexico, New Zealand, 69 The following studies have all found significant signs of nominal wage rigidity: by Bewley (1999), Card and Hyslop (1997), Kahn (1997), Lebow, Saks and Wilson (1999), and Altonji and Devereux (1999) for the United States, by Fortin (1996) for Canada, by Cassino (1995) and Chapple (1996) for New Zealand, by Dwyer and Leong (2000) for Australia, by Castellanos et al (2003) for Mexico, by Kuroda and Yamamoto (2003a, 2003b, 2003c and Kimura and Ueda (2001) for Japan, by Fehr and Goette (2003) for Switzerland, by Bauer et al (2003) and Knoppik and Beissinger (2003) for Germany, by Nickell and Quintini (2001) for the United Kingdom, and by Agell and Lundborg (2003) for Sweden. 70 See, for example, O'Brien (1989) and Hanes (2000).…”
Section: Nominal Considerations In Wage Behaviormentioning
confidence: 99%
“…These distributions are characterized by a bunching of wage changes at exactly zero; there are some wage changes just above zero in these distributions, but almost no wage changes just below. 68 Careful studies have documented such wage stickiness in Australia, Canada, Germany, Japan, Mexico, New Zealand, 69 The following studies have all found significant signs of nominal wage rigidity: by Bewley (1999), Card and Hyslop (1997), Kahn (1997), Lebow, Saks and Wilson (1999), and Altonji and Devereux (1999) for the United States, by Fortin (1996) for Canada, by Cassino (1995) and Chapple (1996) for New Zealand, by Dwyer and Leong (2000) for Australia, by Castellanos et al (2003) for Mexico, by Kuroda and Yamamoto (2003a, 2003b, 2003c and Kimura and Ueda (2001) for Japan, by Fehr and Goette (2003) for Switzerland, by Bauer et al (2003) and Knoppik and Beissinger (2003) for Germany, by Nickell and Quintini (2001) for the United Kingdom, and by Agell and Lundborg (2003) for Sweden. 70 See, for example, O'Brien (1989) and Hanes (2000).…”
Section: Nominal Considerations In Wage Behaviormentioning
confidence: 99%
“…Instead when shocks are positive, or moderately negative so as to require a movement in real wages that does not run into the constraint, real wages are assumed to adjust perfectly to productivity as in the frictionless model, w t = w f t = A t exp( w), and therefore the labor market clears completely. 9 Since it is always the case that wages are bounded below by the ‡exible-wage level, i.e. w t w f t , equation (6) implies that u u t < 1.…”
Section: The Theoretical Frameworkmentioning
confidence: 99%
“…Several papers employ large panels of advanced economies, including Babecky et al in Canada, arguing (in the second paper) that "90% of expected in ‡ation is built into a contract ex ante and over 62% of unexpected in ‡ation in the previous contract is built into the current notional wage adjustment." Bauer et al (2007) …nd that in Germany 30% to 70% of wages settings are subject to downward real wage rigidities; Devicienti et al (2007) show that in Italy that proportion varies between 45% to 65%; Barwell and Schweitzer (2007) suggest that in the UK downward real wage rigidities a¤ect on average 41% of the workers.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of rigidities 2 And not that of job stayers, as it is common in microeconomic studies such as Nickell and Quintini (2003), Bauer et al (2007), Elsby (2009), or Stüber and Beissinger (2012). 3 One implication of these differences, is that prevalent DRWR among individual workers, apparent in micro data by a spike in the wage change distribution at zero, would not imply that the change in average wage is zero.…”
Section: Real Wage Rigidity In Colombiamentioning
confidence: 99%
“…Thus, we present estimates of the    for aggregate industries, aggregate periods, and the full sample, which are likely to be more precise. 5 Finally, we use the simulation method of Holden and Wulfsberg (2008) to test for the statistical significance of our DRWR estimates. This method is considered very powerful for detecting statistical differences between the observed and notional (or free of rigidities) wage change distributions.…”
Section: Notional Distributionsmentioning
confidence: 99%